Prescription for Excellence, by Michael Rachlis - Debbie Fischer (Healthcare Quarterly, 2004)
Dr. Michael Rachlis' Prescription for Excellence is a timely book written for a broad readership. It is both easy to read and easy to understand with respect to the strengths and weaknesses of the healthcare system. The issues facing the Canadian healthcare system are complex and often intractable; however, he is able to analyze the problems, examine the causes and provide examples of innovative best practices and solutions that exist in Canada as well as in other Western countries.